Nasal Airway Evaluation - Perez, Paloma I.; Mei, Christine; Lindsay, Robin W.; Gadkaree, Shekhar K. (Facial Plastic Surgery, 2024)
The nose has several important functions including inspiration, humidification of air, and filtering of allergens. The nose also has a major role in facial harmony as the central focal point. Patients will present to the rhinoplasty surgeon in an effort to fix the inability to breathe through the nose or correct a perceived nasal deformity in the shape of the nose. Choosing the optimal techniques to effectively change the nose requires a thorough understanding of nasal anatomy and nasal mechanics. Ultimately, a complete nasal evaluation is essential in identifying what corresponds to a patient's complaints and how those issues can be addressed surgically or perhaps nonsurgically. When the nose is divided into subunits, and a systematic nasal analysis is performed, one can be confident that all components of the nasal skeleton have been assessed.
Keywords: nasal evaluation; rhinoplasty; outcome measures